Evidence of inequities experienced by the rare disease community with respect to receipt of a diagnosis and access to services: a scoping review of UK and international evidence - Simon Briscoe; Clara Martin Pintado; Katy Sutcliffe; G. J. Melendez-Torres; Ruth Garside; Hassanat M. Lawal; Noreen Orr; Liz Shaw; Jo Thompson Coon (Orphanet Journal of Rare Diseases)
Abstract Background People with a rare disease find it difficult to obtain a diagnosis and access appropriate services. Evidence suggests that this can lead to health inequity amongst the rare disease community, i.e. systemic, unfair and avoidable differences in health opportunities and outcomes. This scoping review aims to identify and describe evidence on health inequities experienced by the rare disease community with regards to receipt of a diagnosis and access to health and social care services. Methods We searched ASSIA, CINAHL, Embase, HMIC, MEDLINE and Social Policy and Practice for relevant studies. Studies were double screened at title and abstract and full-text using pre-specified inclusion criteria. As this research was commissioned by the UK National Institute for Health and Care Research Policy Research Programme, primary studies were limited to UK settings. These were supplemented with international systematic reviews. We also applied a 2010 date limit. Relevant data were extracted and presented narratively and tabulated. Results One hundred thirty-six studies met the inclusion criteria, including 96 primary studies and 40 systematic reviews. The most frequently occurring rare diseases were motor neurone disease, cystic fibrosis and sickle cell disease. Seventeen types of inequity were identified: delayed diagnosis, lack of knowledge amongst clinicians, lack of information provision, limited services provision (across six different services), limited services for undiagnosed conditions, lack of care co-ordination; in addition, inequity was identified relating to place of residence, race/ethnicity, gender, socioeconomic status, age and disability. Conclusion This review has drawn attention to experiences of the rare disease community with respect to receipt of a diagnosis and access to services which are different to experiences in the general population, and within the rare disease community itself. Some of these experiences are clearly attributable to factors which are unfair, avoidable and systemic, particularly those which relate to specific groups in the rare disease community. Experiences relating to delayed diagnosis, lack of knowledge, information, care co-ordination and access to various services, also appeared to indicate inequity. These issues are less likely to be encountered with respect to more common diseases experienced in the general population.